Neutron activation of chlorine in zirconium and zirconium alloys use of the matrix as comparator - Cohen, Isaac Marcos; Mila, María Isabel; Gómez, Conrado Daniel (1981)
Fil: Cohen, Isaac Marcos Comisión Nacional de Energía Atómica; Argentina